Peran Perempuan GKS Jemaat Kaliuda Cabang Kuruwaki dalam Upaya Peningkatan Pendapatan Rumah Tangga Melalui Usaha Pertanian Lahan Kering - Sitaniapessy, Desy Asnath (Universitas Galuh, 2024)
The role of women in the family is not only in domestic affairs, but also related to improving family welfare, in this case women can also take on the role of breadwinner in the family. In Kuruwaki Village, women also take part in efforts to increase family income through agricultural businesses. Through this research, it aims to analyze the role of women farmers who work in efforts to improve the household economy and analyze the effect of farm income on household finances. The scope of this research only takes the object of women involved in farmer groups in Kuruwaki Village, Pahunga Lodu Sub-district. The limitation of the problem is only seen in the role of women in efforts to improve the family economy in Kuruwaki village. The benefit of this research is to know the role of women in improving the family economy and the extent to which farming businesses run by groups provide benefits in improving the family economy. The method used is descriptive qualitative. This research shows that the dry land farming business undertaken by women has a good impact on improving the family economy, besides that the results of this study are expected to produce new perspectives and attitudes that appreciate women in the community towards women's efforts in improving the family economy.